Laboratory investigation into the effects of fibers on bituminous mixtures - Toraldo, Emanuele; Mariani, Edoardo; Malvicini, Sara (Journal of Civil Engineering and Management, 2014)
The growing need for high quality bituminous mixtures in road construction, rehabilitation and maintenance is currently satisfied by means of techniques to produce polymer-modified bitumen, or by the addition of additives to mixtures during in-plant mixing operations. A rigorous rheological approach in the study of the bitumen modification process enables researchers to rationally compare different modifying agents and to evaluate their relative efficiency for specific field applications. As far as additives are concerned, the binder is not the only element involved in the evaluation; both binding mastics and bituminous mixtures must be evaluated to get a complete understanding of the characteristics. Moreover, the advantages that may stem from the use of fibers should be carefully taken into consideration since they may offer alternative strategies for the enhancement of bituminous mixtures. As a result of these observations, the authors have devised an experimental research project focused on the analysis of the effects of different types and dosages of cellulose-based fibers on the main performance-related properties of bituminous road materials: compaction properties, volumetric characteristics and mechanical performance. This paper provides an overview of the results obtained and some details of the specific protocols followed during the research project.